Tashkent Period Of The Turkestan Collection (Global Scientific Review, 2024)
The main part of the “Turkestan Collection” (volumes from 1 to 416) was prepared in St. Petersburg under the leadership of the famous Russian bibliographer Vladimir Mezhov from 1867 to 1887. Then the compilation of new volumes of the collection resumed only in 1907 in Tashkent. By 1910, under the leadership of bibliographer N.V.Dmitrovsky, 127 volumes (from 417 to 543) were published, and in 1911-1916, under the leadership of orientalist Alexander Semenov, another 48 (from 544 to 591). The last three volumes of the “Turkestan Collection” (from 592 to 594) were compiled under the leadership of bibliographer E.K.Betger in 1939. In addition, at different times several catalogs and indexes to the materials in the collection were compiled. This article provides information on the use of the Turkestan Collection of the Tashkent period as a valuable documentary source for the history of colonial Turkestan.